Method for regenerating battery-grade iron phosphate from phosphorus iron slag after lithium extraction
By strengthening the leaching and deep decomposition steps of phosphate iron slag, the problem of phosphate iron slag resource utilization after lithium extraction is solved, efficient iron phosphate regeneration is achieved, and the market is achieved, resource waste and solid waste problems are avoided, and market demand is met.
Patent Information
- Application Number
- CN202411160195.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to effectively utilize the ferrous slag after lithium extraction, resulting in waste of resources and the quality of regenerated ferrous phosphate cannot meet market demand.
By strengthening the leaching of phosphate iron slag, one-step deep impurity removal and iron phosphate regeneration steps, the leaching rate of phosphorus and iron elements reached 99%, and the impurity removal rate was as high as 98.93%, and battery-grade iron phosphate was prepared by co-precipitation and calcination.
The quality of regenerated iron phosphate reaches the commercial standard, reduces the cost of iron phosphate regeneration, avoids solid waste storage and landfill, improves resource utilization, and deeply removes Al and Cu impurities, and the obtained product has high purity and meets the market. Use requirements for battery-grade iron phosphate sale.
Smart Images

Figure CN119218951A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling waste lithium-ion batteries, and in particular relates to a method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction. Background Art
[0002] In the field of lithium-ion batteries, lithium iron phosphate power batteries are gradually increasing in the new energy vehicle market due to their excellent cycle performance, good safety performance and low manufacturing cost. However, the cycle life of power batteries is not infinite, and they will face the problem of retirement and scrapping after reaching a certain service life. At present, my country is at the starting point of a large-scale retirement wave of waste lithium iron phosphate power batteries, and many companies are planning the recycling and resource utilization of waste lithium iron phosphate batteries.
[0003] At present, the methods used by enterprises for recycling and resource utilization of waste lithium iron phosphate batteries are mainly divided into physical methods and wet methods. The physical method mostly uses high-purity black powder from waste batteries, and mixes additives for roasting to prepare lithium iron phosphate recycled materials. Its process is short and the manufacturing cost is low, but the repaired recycled materials are difficult to reach the performance level of raw materials. The wet method is mainly divided into selective leaching for lithium extraction and full-element leaching for recycling. At present, the selective leaching route for lithium extraction is mature, and many companies have implemented cases, but the ferrophosphorus slag after lithium extraction is difficult to use and is usually stored or landfilled as solid waste. Ferrophosphorus slag contains considerable phosphorus and iron resources. Storage or landfill treatment will cause a huge waste of resources. As waste lithium iron phosphate batteries gradually increase in volume, it is urgent to develop technology for efficient utilization of ferrophosphorus slag.
[0004] Nowadays, the utilization of ferrophosphorus slag resources has gradually attracted widespread attention, but the quality requirements of ferrophosphorus slag are relatively high. For example, CN117460694A provides a method for preparing ferric phosphate by decarbonization of ferrophosphorus slag. The carbon content of the ferrophosphorus slag used is only about 5%. It is speculated that it is lithium iron phosphate positive electrode powder lithium extraction slag, which has a simple composition, while the battery waste powder has a complex composition and a carbon content of 20%-30%, which is not suitable for decarbonization and regeneration of battery-grade ferric phosphate. CN116425136B proposes a method for purifying and recovering battery-grade ferric phosphate from ferrophosphorus slag after lithium extraction. Although the use of materials such as aluminum removal agents and fluoride salts is avoided, the quality of the regenerated battery-grade ferric phosphate is low and can no longer meet the existing market demand. Based on this, the present invention uses ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery black powder as raw material, and develops a method for regenerating battery-grade ferric phosphate from ferrophosphorus slag after lithium extraction by strengthening ferrophosphorus slag leaching, one-step deep impurity removal, and ferric phosphate regeneration, so as to achieve the quality of regenerated ferric phosphate reaching the existing market standard. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a simple and efficient method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery black powder. By strengthening the leaching reaction of ferrophosphorus slag, the leaching rate of phosphorus and iron elements can reach 99%, and the impurity removal rate can be as high as 98.93% through one-step impurity removal, and the ferrophosphorus loss rate is as low as 2.44%. Subsequently, battery-grade iron phosphate is regenerated through co-precipitation and roasting.
[0006] To achieve the above object, the technical solution adopted by the present invention is: A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps: (1) Waste residue leaching: deionized water is added to the phosphorus iron slag after lithium extraction to adjust the initial solid-liquid ratio, sulfuric acid is added after stirring to adjust the pH, and then a reducing agent is added to react, and the reactants are filtered to obtain a leachate rich in iron and phosphorus; (2) Impurity removal: pH regulator and impurity remover are added to the leaching solution, and impurity-removing liquid is obtained after the reaction is completed.
[0007] (3) Synthesis of iron phosphate: After adjusting the iron-phosphorus ratio of the impurity removal liquid, a surface dispersant, an oxidant and a pH adjuster are added, and dihydrate iron phosphate is obtained after the reaction. The dihydrate iron phosphate is roasted to obtain battery-grade iron phosphate.
[0008] Furthermore, in step (1), the initial solid-liquid ratio is 100-300 g / L, the stirring time is 50-70 min, the reaction pH is 1-3, and the reaction time is 1-3 h.
[0009] Furthermore, in step (1), the initial solid-liquid ratio is 150-250 g / L, the stirring time is 60 min, the reaction pH is 1.5-2, and the reaction time is 1.5-2.5 h.
[0010] Furthermore, in step (1), the reducing agent is one or more of iron powder, hydrazine hydrate and sodium metabisulfite.
[0011] Furthermore, in step (1), the amount of the reducing agent used is 0.2-0.4 times the molar amount of iron in the ferrophosphorus slag.
[0012] Furthermore, in step (2), the pH regulator is one or more of ammonia water, sodium hydroxide or sodium carbonate solution, and the impurity remover is one or more of iron powder, sodium fluoride and ammonium fluoride; by using the impurity remover, impurities such as copper, aluminum and titanium in the leachate are deeply removed.
[0013] Furthermore, the pH regulator is ammonia water, the oxidant is hydrogen peroxide, and the impurity remover is iron powder and fluoride; the amount of the iron powder is 1-2 times the molar amount of copper in the ferrophosphorus slag, and the amount of the fluoride is 1-6 times the molar amount of aluminum in the ferrophosphorus slag.
[0014] Furthermore, in step (2), a pH adjusting agent is used to adjust the pH to 2-4, and the reaction time is 50-70 min.
[0015] Furthermore, in step (2), a pH adjuster is used to adjust the pH to 3-4.
[0016] Furthermore, in step (3), the iron-phosphorus molar ratio is 0.9-1.1:1.
[0017] Furthermore, the iron-phosphorus molar ratio is 0.95-1.1:1.
[0018] Furthermore, in step (3), the surfactant is one or more of cetyltrimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP) and sodium dodecyl sulfate (SDS), the pH adjuster is one or more of ammonia water, sodium hydroxide or sodium carbonate solution, and the oxidant is one or more of hydrogen peroxide, oxygen and ozone.
[0019] Furthermore, the pH regulator is ammonia water, and the oxidant is hydrogen peroxide.
[0020] Furthermore, in step (3), the amount of the oxidant used is 0.5-0.7 times the molar amount of iron in step (3).
[0021] Furthermore, in step (3), the reaction temperature is 80-100°C and the reaction time is 2-6h.
[0022] Furthermore, in step (3), the reaction temperature is 80-90°C and the reaction time is 3-6h.
[0023] Furthermore, in step (3), the calcination temperature is 550-700°C, the heating rate is 5-10°C / min, and the holding time is 4-8h.
[0024] Furthermore, in step (3), the calcination temperature is 600-700°C, the heating rate is 5-8°C / min, and the holding time is 5-7h.
[0025] Compared with the prior art, the present invention has the following beneficial effects: The method for regenerating battery-grade iron phosphate provided by the present invention strengthens the leaching reaction of phosphorus iron slag without introducing impurity elements, and the leaching rate of phosphorus and iron elements can reach 99%; the purified liquid is prepared by one-step impurity removal, and the impurity removal rate is as high as 98.93%, and the phosphorus iron loss rate is as low as 2.44%; the purified liquid is synthesized into battery-grade iron phosphate by a regulator. The present invention uses the slag after lithium extraction from waste lithium iron phosphate battery black powder as a raw material for regenerating battery-grade iron phosphate, which can not only reduce the cost of iron phosphate regeneration, but also effectively avoid the problem of solid waste storage and landfill, improve resource utilization, and realize the deep regeneration and green environmental protection cycle of waste lithium battery resources; at the same time, the present invention realizes the deep removal of Al and Cu impurities through this method, so that the obtained product has high purity and can fully meet the use requirements of commercially available battery-grade iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0027] In order to further illustrate the present invention, the technical scheme of the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0028] The raw materials used in the following examples and comparative examples are ferrophosphorus slag after lithium extraction from waste lithium iron phosphate battery black powder, and the main element content analysis is shown in Table 1.
[0029] Table 1 Main element content of lithium-phosphorus iron slag
[0030] Embodiment 1: like Figure 1 As shown, a method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction comprises the following steps: (1) Waste residue leaching: deionized water was added to 500 g of ferrophosphorus slag after lithium extraction, and the initial solid-liquid ratio was adjusted to 200 g / L. After mixing for 60 min, 225 g of concentrated sulfuric acid was added to adjust the pH to 1.7, and then 0.3 times the molar ratio of hydrazine hydrate based on the iron in the ferrophosphorus slag was added. After reacting for 2 h, a ferrophosphorus leaching solution was obtained, and the reactants were filtered to obtain a leaching solution rich in iron and phosphorus; (2) Primary impurity removal: 500 g of leachate was added with 2.23 g of iron powder and stirred for 30 min to remove copper, followed by adding 25% ammonia water to adjust the pH to 3.5, and finally adding 4.67 g of ammonium fluoride and reacting at 55 °C for 1 h to obtain an impurity-removed solution; (3) Synthesis of ferric phosphate: ferrous sulfate was added to the impurity removal liquid to adjust the iron-phosphorus ratio in the solution to 1.09:1, followed by the addition of 1% CTAB dispersant, and the addition of 0.6 times the molar amount of hydrogen peroxide based on iron. The pH was adjusted to 1.5 with aqueous ammonia, and then stirred at 85°C for 4 h to obtain ferric phosphate dihydrate. Finally, the washed and dried ferric phosphate dihydrate was placed in a box furnace, heated to 650°C at a rate of 7°C / min, and then kept at this temperature for 6 h to obtain battery-grade ferric phosphate.
[0031] The test results of the leaching solution, impurity removal solution and regenerated iron phosphate in this example are shown in Table 2-4.
[0032] Calculations on the impurity removal liquid revealed that the copper, aluminum and titanium impurity removal rates were 99.91%, and the phosphorus and iron loss rate was 2.47%. Testing of the prepared iron phosphate revealed that the battery-grade iron phosphate met commercial standards, with an iron content of 36.46% and a phosphorus content of 20.89%. The impurity indicators met commercial standards, with an iron-phosphorus ratio of up to 0.968.
[0033] Embodiment 2: A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps: (1) Waste residue leaching: deionized water was added to 500 g of ferrophosphorus slag after lithium extraction, and the initial solid-liquid ratio was adjusted to 200 g / L. After mixing for 60 min, 225 g of concentrated sulfuric acid was added to adjust the pH to 1.7, and then 0.3 times the molar ratio of hydrazine hydrate based on the iron in the ferrophosphorus slag was added. After reacting for 2 h, a ferrophosphorus leaching solution was obtained, and the reactants were filtered to obtain a leaching solution rich in iron and phosphorus; (2) Primary impurity removal: 500 g of leachate was added with 2.23 g of iron powder and stirred for 30 min to remove copper, followed by adding 25% ammonia water to adjust the pH to 3.5, and finally adding 4.67 g of ammonium fluoride and reacting at 55 °C for 1 h to obtain an impurity-removed solution; (3) Synthesis of ferric phosphate: 85% phosphoric acid was added to the impurity removal solution to adjust the iron-phosphorus ratio in the solution to 1:1, followed by the addition of 1% CTAB dispersant, and the addition of 0.6 times the molar amount of hydrogen peroxide based on iron. The pH was adjusted to 1.5 with aqueous ammonia, and then stirred at 85°C for 4 h to obtain ferric phosphate dihydrate. Finally, the washed and dried ferric phosphate dihydrate was placed in a box furnace, heated to 650°C at a rate of 7°C / min, and then kept at this temperature for 6 h to obtain battery-grade ferric phosphate.
[0034] The test results of the leaching solution, impurity removal solution and regenerated iron phosphate in this example are shown in Table 2-4.
[0035] Calculation of the impurity removal liquid showed that the copper, aluminum and titanium impurity removal rates were 99.93%, and the phosphorus and iron loss rate was 2.44%. Testing of the prepared iron phosphate showed that the battery-grade iron phosphate met the commercial standards, with an iron content of 36.17% and a phosphorus content of 20.81%. The impurity indicators met the commercial standards, and the iron-phosphorus ratio was moderate, reaching 0.964.
[0036] Embodiment 3: A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps: (1) Waste residue leaching: deionized water was added to 500 g of ferrophosphorus slag after lithium extraction, and the initial solid-liquid ratio was adjusted to 200 g / L. After mixing for 60 min, 225 g of concentrated sulfuric acid was added to adjust the pH to 1.7, and then 0.3 times the molar ratio of hydrazine hydrate based on the iron in the ferrophosphorus slag was added. After reacting for 2 h, a ferrophosphorus leaching solution was obtained, and the reactants were filtered to obtain a leaching solution rich in iron and phosphorus; (2) Primary impurity removal: 500 g of leachate was added with 2.23 g of iron powder and stirred for 30 min to remove copper, followed by adding 25% ammonia water to adjust the pH to 3.5, and finally adding 4.67 g of ammonium fluoride and reacting at 55 °C for 1 h to obtain an impurity-removed solution; (3) Synthesis of ferric phosphate: 85% phosphoric acid was added to the impurity removal solution to adjust the iron-phosphorus ratio in the solution to 1:1.09, followed by the addition of 1% CTAB dispersant, and the addition of 0.6 times the molar amount of hydrogen peroxide based on iron. The pH was adjusted to 1.5 with aqueous ammonia, and then stirred at 85°C for 4 h to obtain ferric phosphate dihydrate. Finally, the washed and dried ferric phosphate dihydrate was placed in a box furnace, heated to 650°C at a rate of 7°C / min, and then kept at this temperature for 6 h to obtain battery-grade ferric phosphate.
[0037] The test results of the leaching solution, impurity removal solution and regenerated iron phosphate in this example are shown in Table 2-4.
[0038] Calculation of the impurity removal liquid showed that the copper, aluminum and titanium impurity removal rate was 99.89%, and the phosphorus and iron loss rate was 2.58%. Testing of the prepared iron phosphate showed that the battery-grade iron phosphate met the commercial standards, with an iron content of 36.24% and a phosphorus content of 20.90%. The impurity indicators met the commercial standards, and the iron-phosphorus ratio was relatively low, reaching 0.961.
[0039] Comparative Example 1: A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps: (1) Waste residue leaching: deionized water was added to 500 g of ferrophosphorus slag after lithium extraction, and the initial solid-liquid ratio was adjusted to 200 g / L. After mixing for 60 min, 225 g of concentrated sulfuric acid was added to adjust the pH to 1.7, and then 0.3 times the molar ratio of hydrazine hydrate based on the iron in the ferrophosphorus slag was added. After reacting for 2 h, a ferrophosphorus leaching solution was obtained, and the reactant was filtered to obtain a leaching solution rich in iron and phosphorus; (2) Primary impurity removal: 500 g of the leachate was added with 2.23 g of iron powder and stirred for 30 min to remove copper, followed by adding 25% ammonia water to adjust the pH to 4, and finally adding 4.67 g of ammonium fluoride and reacting at 55 °C for 1 h to obtain an impurity-removed solution; (3) Synthesis of ferric phosphate: ferrous sulfate was added to the impurity removal liquid to adjust the iron-phosphorus ratio in the solution to 1.09:1, followed by the addition of 1% CTAB dispersant, and the addition of 0.6 times the molar amount of hydrogen peroxide based on iron. The pH was adjusted to 1.5 with aqueous ammonia, and then stirred at 85°C for 4 h to obtain ferric phosphate dihydrate. Finally, the washed and dried ferric phosphate dihydrate was placed in a box furnace, heated to 650°C at a rate of 7°C / min, and then kept at this temperature for 6 h to obtain battery-grade ferric phosphate.
[0040] The test results of the leaching solution, impurity removal solution and regenerated iron phosphate of this comparative example are shown in Table 2-4.
[0041] Through calculation of the impurity removal liquid, it can be obtained that the copper, aluminum and titanium impurity removal rate is 99.98%, and the phosphorus and iron loss rate is 9.86%. The phosphorus and iron loss is too large, which is not conducive to the efficient utilization of resources. Through testing the prepared iron phosphate, it can be known that the battery-grade iron phosphate meets the commercial standards, with an iron content of 36.38% and a phosphorus content of 20.85%. The impurity indicators meet the commercial standards, and the iron-phosphorus ratio is relatively high, reaching 0.967.
[0042] Comparative Example 2: A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, comprising the following steps: (1) Waste residue leaching: deionized water was added to 500 g of ferrophosphorus slag after lithium extraction, and the initial solid-liquid ratio was adjusted to 200 g / L. After mixing for 60 min, 225 g of concentrated sulfuric acid was added to adjust the pH to 1.7, and 0.3 times the molar ratio of hydrazine hydrate based on the iron in the ferrophosphorus slag was added. After reacting for 2 h, a ferrophosphorus leaching solution was obtained, and the reactant was filtered to obtain a leaching solution rich in iron and phosphorus; (2) Primary impurity removal: 500 g of leachate was added with 2.23 g of iron powder and stirred for 30 min to remove copper, followed by adding 25% ammonia water to adjust the pH to 3, and finally adding 4.67 g of ammonium fluoride and reacting at 55 °C for 1 h to obtain a de-impurity solution; (3) Synthesis of ferric phosphate: ferrous sulfate was added to the impurity removal liquid to adjust the iron-phosphorus ratio in the solution to 1.09:1, followed by the addition of 1% CTAB dispersant, and the addition of 0.6 times the molar amount of hydrogen peroxide based on iron. The pH was adjusted to 1.5 with aqueous ammonia, and then stirred at 85°C for 4 h to obtain ferric phosphate dihydrate. Finally, the washed and dried ferric phosphate dihydrate was placed in a box furnace, heated to 650°C at a rate of 7°C / min, and then kept at this temperature for 6 h to obtain battery-grade ferric phosphate.
[0043] The test results of the leaching solution, impurity removal solution and regenerated iron phosphate of this comparative example are shown in Table 2-4.
[0044] Calculation of the impurity removal liquid showed that the copper, aluminum and titanium impurity removal rate was 90.65%, and the phosphorus and iron loss rate was 2.11%. Testing of the prepared iron phosphate showed that the battery-grade iron phosphate did not meet the commercial standards, with an iron content of 36.35%, a phosphorus content of 20.82%, and aluminum and titanium impurity indicators exceeding the standard, with an iron-phosphorus ratio of 0.968.
[0045] Table 2-4 shows the element detection results of the leaching solution, impurity removal solution and regenerated iron phosphate in the above examples.
[0046] Table 2 Statistics of main element contents in leachate Components Fe P Al Cu Ti content 4.71% 2.46% 0.31% 0.26% 0.03% Table 3 Statistics of main elements content in impurity removal liquid
[0047] Table 4 Statistics of main element contents of regenerated iron phosphate
[0048] It can be seen from the above table that the electronic-grade iron phosphate prepared by the method of the present invention meets market standards, and can deeply remove ferrophosphorus slag with high metal ions such as copper content to obtain higher-purity iron phosphate, thereby realizing deep recycling and green environmental protection cycle of waste lithium battery resources.
[0049] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction, characterized in that: The method comprises the following steps: (1) Waste residue leaching: deionized water is added to the phosphorus iron slag after lithium extraction to adjust the initial solid-liquid ratio, sulfuric acid is added after stirring to adjust the pH, and then a reducing agent is added to react, and the reactants are filtered to obtain a leachate rich in iron and phosphorus; (2) removing impurities: adding a pH regulator and an impurity remover to the leaching solution to obtain an impurity-removing solution; (3) Synthesis of iron phosphate: The ratio of iron to phosphorus in the impurity removal solution is adjusted, and a surface dispersant, an oxidant, and a pH adjuster are added to obtain iron phosphate dihydrate after the reaction. The iron phosphate dihydrate is then roasted to obtain battery-grade iron phosphate.
2. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (1), the initial solid-liquid ratio is 100-300 g / L, the reaction pH is 1-3, and the reaction time is 1-3 h.
3. The method for regenerating battery-grade ferric phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (1), the reducing agent is one or more of iron powder, hydrazine hydrate and sodium pyrosulfite.
4. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (1), the amount of the reducing agent used is 0.2-0.4 times the molar amount of iron in the ferrophosphorus slag.
5. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (2), the pH regulator is one or more of ammonia water, sodium hydroxide or sodium carbonate solution, and the impurity remover is one or more of iron powder, sodium fluoride and ammonium fluoride.
6. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (2), a pH adjuster is used to adjust the pH to 2-5.
7. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (3), the iron-phosphorus molar ratio is 0.9-1.1:
1.
8. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (3), the surfactant is one or more of cetyltrimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP) and sodium dodecyl sulfate (SDS), the pH adjuster is one or more of ammonia water, sodium hydroxide or sodium carbonate solution, and the oxidant is one or more of hydrogen peroxide, oxygen and ozone.
9. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (3), the reaction temperature is 80-100°C and the reaction time is 2-6h.
10. The method for regenerating battery-grade iron phosphate from ferrophosphorus slag after lithium extraction according to claim 1, characterized in that: In step (3), the calcination temperature is 550-700°C, the heating rate is 5-10°C / min, and the holding time is 4-8h.
Citation Information
Patent Citations
Method for recovering iron phosphate from iron-phosphorus slag after lithium extraction of lithium iron phosphate battery
CN111646447A
Method for preparing battery-grade iron phosphate by recovering phosphorus iron slag after lithium extraction
CN117602604A
Cited By
Method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate
CN119841293A
Method for separating and recycling ferrophosphorus in battery recycling byproduct ferrophosphorus slag
CN120157188A
Method for separating and recovering phosphorus and iron in phosphorus-iron slag as a byproduct of battery recycling
CN120157188B
Method for treating iron-containing waste residue by using waste to treat waste and battery-grade iron phosphate
CN120841470A
Method for recovering and preparing battery-grade iron phosphate from lithium-extracted ferrophosphorus slag
CN122916083A